FINANCIAL INSTRUMENTS OF THE RESIDENTIAL REAL ESTATE MARKET DEVELOPMENT IN THE PRC: LESSONS FOR UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The residential real estate market at the beginning of the 21st century. became the driving force behind the growth of the PRC economy, giving a powerful impetus to the development of related types of economic activity. The article presents the characteristics of its features, including mechanisms for supporting real estate investments, identifies problems and prospects for the functioning of the housing market, taking into account the risks of a repeat of the mortgage and financial crises according to the US scenario; defines the role of the state in regulating the residential real estate market of the PRC. The results of the study can be useful in assessing the situation on the residential real estate market and in the construction industry of Ukraine.The purpose of the article. The purpose of this study is to determine the financial instruments of the development of the residential real estate market of China and adapt foreign experience to domestic realities.Methods. In conducting the study, general scientific and special methods were used, in particular: retrospective analysis - to study the features of state support for the residential real estate market of the PRC; systemic approach - to consider investment potential as an element of the real estate market recovery system; methods of generalization and comparison - in order to systematize scientific views on the object of research, to substantiate theoretical aspects of the need to increase investment potential in the real estate market.Results. China's experience demonstrates that active state support for the residential real estate market can have a positive impact on its development and ensure the availability of housing for the population. Ukraine should take these aspects into account in its policy, adapting them to local conditions and needs.Conclusions. State support in China, in particular through subsidies and soft loans, has demonstrated its effectiveness in ensuring the availability of housing. Ukraine should consider the possibility of introducing similar programs to support young families and low-income segments of the population. At the same time, housing price control programs in China have helped to avoid speculation in the market. At the same time, China is actively building social housing for low-income citizens. In general, China's experience demonstrates the importance of a comprehensive approach to the development of the real estate market, which includes financial support, regulation, social programs and infrastructure investments, which should be taken into account when developing an integrated strategy of state support in Ukraine.
Keywords: financial instruments, mortgage lending, residential property taxation, residential property market, construction, housing prices, economic growth, financial subsidies, China.